Neural networks in the advisory system for repairs of industrial concrete floors - Gajzler, Marcin (Computer Assisted Methods in Engineering and Science, 2011)
An advisory system for repairs of industrial concrete floors is a supporting tool for making material and technological decisions in the sphere of problems of recurrent character. The presented advisory system has the character of a hybrid system. Various elements of tools from the artificial intelligence group have been used in it. Artificial neural networks are of particular importance for functioning of the system. They act as an inference engine. The article presents, inter alia, an approach in the sphere of teaching artificial neural networks on the basis of an expert's knowledge, as well as utilization of fuzzy sets for data transformation and for increasing the size of the case set. The conclusions indicate the profits resulting from utilization of artificial neural networks like speed of operation or absence of the need to possess complete knowledge.